JEWELRY DESIGN: ARTISTIC EXPRESSIVENESS AND COMPOSITIONAL AND CONSTRUCTIVE SHAPING OF HEAD BUILDER OF PRECIOUS INSERTS - Остапенко, Н. В.; Стонога, Д. В. (Art and Design, 2023)
Aim. The study is devoted to the analysis of artistic expressiveness and compositional and constructive characteristics of settings of precious and semiprecious inserts for jewelry. Methodology. The study of varieties of compositional and constructive shaping of bindings is based on a comprehensive approach, general scientific research methods. Visual-analytical, system-structural approaches, methods of comparison, analysis and synthesis, generalization, and grouping elements of fixing products are used. The CorelDRAW Technical Suite 2022 graphic editor is used to perform drawings. Results. Specific terminological definitions of various concepts of the constituent elements of jewelry, namely settings of precious inserts, are given. Based on the analysis of modern varieties of jewelry, the fact of the influence of the design, shape, and setting elements on the design of modern jewelry is proved. The relationship between the product and The Shape of the clips of jewelry inserts and their influence on the artistic expressiveness of jewelry is analyzed. On the example of rings that are diverse in design, their stylistic and artistic features are considered. The main requirements for structural elements of fixing design inserts in modern jewelry are formulated. Scientific novelty. The relationship between the characteristic structures, composition, shape of the pin and the jewelry is comprehensively attested. The article summarizes the types of pinning of precious and semiprecious stones in modern jewelry in accordance with classical, specific and mixed types. Practical significance. Modern types of settings are listed and described, their forming parts and technical features are characterized. Their artistic expressiveness is clearly demonstrated through the relationship with finishing elements on the example of modern rings. Varieties of the main classical forms of cutting precious stones are listed and graphically presented. Recommendations are given for choosing the type of settings, its compositional and structural solution, depending on the type of stone, its shape, size, cut, and their number in the product.